2018
DOI: 10.1108/compel-07-2017-0297
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling on partial discharge in HVDC XLPE cable

Abstract: PurposeHigh voltage direct current (HVDC) cable is an important part in the electric power transmission and distribution systems. However, very little research has been carried out on partial discharge under direct current (DC) conditions. Niemeyer’s model has been widely used under alternating current (AC) conditions. This paper aims to intend to modify the Niemeyer’s model considering both electric field and charge dynamics under DC conditions, and therefore proposes a numerical model describing partial disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The charges left on the surface of the cavity due to the previous PD may decay in time through recombination, diffusion, and conduction. Under AC voltage, recombination is the dominant process [43]. In analytical‐based models [27], the surface charge decay rate is usually modelled as an exponential decay function, exp(− t/τ ins ), where t (s) is the time elapsed since the last PD and τ ins (s) is the material time constant that depends on the void surface conductivity.…”
Section: Pd Fea Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The charges left on the surface of the cavity due to the previous PD may decay in time through recombination, diffusion, and conduction. Under AC voltage, recombination is the dominant process [43]. In analytical‐based models [27], the surface charge decay rate is usually modelled as an exponential decay function, exp(− t/τ ins ), where t (s) is the time elapsed since the last PD and τ ins (s) is the material time constant that depends on the void surface conductivity.…”
Section: Pd Fea Modelsmentioning
confidence: 99%
“…In [43], an EC FEA model was implemented for PD simulations under DC conditions and was applied for a case of study in a HV DC XLPE cable. Surface charge decay due to charge recombination by charge propagation on the cavity wall was neglected because, at DC voltage, the electric field due to the surface charge is always against the applied electric field, there is no polarity change.…”
Section: Pd Fea Modelsmentioning
confidence: 99%
“…Through a mathematical procedure, the minimum theoretical discharge initiation voltage can be determined, however, as PD will not initiate at this voltage, this value should be increased in order to promote the PD appearance during laboratory tests. In [68], the analytical approach is used for determining the discharge characteristics at DC voltage and it was found that for this case the electrical conductivity plays a fundamental role in the inception voltage, repetition rate and discharge magnitudes, however there is not experimental validation.…”
Section:  mentioning
confidence: 99%
“…Therefore, it seems that the surface charge decay through insulator volume becomes the predominant way. He et al held that the recovery of cavity field after a discharge is only attributed to the charge decay through volume conduction, and constructed a PD simulation model under DC voltage [85]. In our previous research, surface charge dynamic distributions produced by DC PDs were measured [12].…”
Section: Differences Of Pd Modeling Under Ac and DC Voltagesmentioning
confidence: 99%